Disorders of esophageal clearance in gastroesophageal reflux disease and option of their treatment - O. A. Storonova; A. S. Trukhmanov; N. L. Dzhahaya; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To estimate esophageal clearance in patients with reflux-esophagitis (RE) and its changes at intake of «Smecta®» in standard dose. Material and methods. Overall 30 patients whose symptoms included heartburn (100%), burning chest pain (70%), belching (30%) were enrolled in original study. Of them 16 were women and 14 – men, mean age – 46,02 years (22 to 74 years). The body mass index in group was elevated (mean —25,0 [24,2; 28,6] kg/m2). Patients underwent esophagogastroduodenoscopy (EGDS), 24-hour pH-metry, X-ray investigation with barium meal, investigation of esophageal motor function. Results. According to the data of EGDS, pH-metry, non-erosive reflux disease (NERD) was found in 21 patients (70%), erosive GERD — in 9 (30%). At investigation of motor function decrease of amplitude and nonperistaltic waves are registered in 33,3 and 13,3% of patients respectively, esophageal spasm – in 20%, and tertiary contractions – in 36,7% of cases. In 46,7% of patients delay in clearance of the esophagus up to 9 min on average was registered [3,5; 15], all patients with erosive RE had increased clearance time (р<0,05). At catarrhal RE delayed clearance was observed in patients with hypermotor disorders (р<0,05), normal scores of clearance – in patients without severe disorders of motor activity of the esophagus, 2,5 min mean [1; 3]. On a background of intake of smecta in patients with prolonged clearance its time decreased to 3 min [1; 4]. Rate of refluxate elimination from the esophagus at delayed natural clearance was 0,9•10–2 U/s, on background of smecta intake - 13•10–2 U/s, i.e. 14 times faster. Conclusions. Disorders of motor activity of the esophagus and salivation impact to decrease in esophageal clearance. Intake of smecta accelerates process of refluxate elimination from the esophagus for one order more and restores normal scores of рН, reducing duration of reflux and exposure to aggressive contents of the stomach to the esophagus in patients with NERD and GERD equally. Decrease of intensity of heartburn and the arrest of retrosternal pain is found in 80 and 72% of patients respectively. Thus of patients with catarrhal RE improvement was achieved in 93% of cases. Thus, smecta can be recommended as monotherapy at catarrhal RE and in composition of complex treatment at erosive GERD.